Immunology of naturally transmissible tumours. Issue 1 (January 2015) - Siddle, Hannah V.; Kaufman, Jim
Summary Naturally transmissible tumours can emerge when a tumour cell gains the ability to pass as an infectious allograft between individuals. The ability of these tumours to colonize a new host and to cross histocompatibility barriers contradicts our understanding of the vertebrate immune response to allografts. Two naturally occurring contagious cancers are currently active in the animal kingdom, canine transmissible venereal tumour (CTVT), which spreads among dogs, and devil facial tumour disease (DFTD), among Tasmanian devils. CTVT are generally not fatal as a tumour‐specific host immune response controls or clears the tumours after transmission and a period of growth. In contrast, the growth of DFTD tumours is not controlled by the Tasmanian devil's immune system and the disease causes close to 100% mortality, severely impacting the devil population. To avoid the immune response of the host both DFTD and CTVT use a variety of immune escape strategies that have similarities to many single organism tumours, including MHC loss and the expression of immunosuppressive cytokines. However, both tumours appear to have a complex interaction with the immune system of their respective host, which has evolved over the relatively long life of these tumours. The Tasmanian devil is struggling to survive with the burden of this disease and it is only with an understanding of how DFTD passes between individuals that a vaccine might be developed. Further, an understanding of how these tumours achieve natural transmissibility should provide insights into general mechanisms of immune escape that emerge during tumour evolution.